Optimization of fresh produce delivery path based on C-W saving algorithm - Zhao, Wanru; Geng, Qi (International Journal of Global Economics and Management, 2024)
Because fresh agricultural products have the characteristics of difficulty in preserving freshness, short shelf life, and are perishable and fragile, so they have extremely high requirements for warehousing, distribution, and other multiple links, and their distribution costs have caused some economic pressure on Z. To reduce the distribution costs of Z's distribution centers and to maximize the satisfaction of customers' needs, it is very important to carry out reasonable planning of the distribution paths. How to scientifically and reasonably formulate the vehicle distribution plan and arrange the distribution path program, shorten the time of fresh agricultural products in transit and reduce the company's logistics and distribution costs, maximize customer satisfaction, and accurately and timely provide customers with high-quality fresh agricultural products and high-quality distribution services are of great significance. In this paper, by summarizing the existing literature on the optimization of the distribution path of fresh agricultural products cold chain logistics, the C.W saving algorithm is used to optimize the path of the distribution center of Z company.